The Role of Dentists in COVID-19 Is Beyond Dentistry: Voluntary Medical Engagements and Future Preparedness - Seneviratne, Chaminda Jayampath; Lau, Matthew Wen Jian; Goh, Bee Tin (Frontiers in Medicine, 2020)
The emergence of highly infectious novel coronavirus SARS-CoV-2 has led to a global pandemic of COVID-19. Since the outbreak of COVID-19, worldwide healthcare systems have been severely challenged. The rapid and explosive surge of positive cases has significant increased the demand for medical care. Herein we provide a perspective on the role of dentists can play in voluntary medical assistance and future preparedness for a similar pandemic situation. Though dentists and physicians have different scopes of practice, their trainings share many similarities. Hence, dental professionals, with their knowledge of basic human science and sterile surgical techniques are an invaluable resource in the COVID-19 pandemic response. Overall, it is commendable that many dentists have risen to the challenge in the fight against COVID-19. For example, in Singapore, National Dental Centre Singapore (NDCS) deployed dental clinicians as well as volunteers from research field to screen for suspected cases, provide consultations as well as conduct swabbing operations. Dental practice will be considerably changed in the post-COVID era. There is a greater need for refresher courses for the practicing dentists on new infection control strategies. Moreover, the curriculum in dental schools should also be expanded to include competencies in pandemic and disaster relief. In addition, voluntary medical work should be made a part of the community dentistry curriculum. This volunteerism will leave a positive impact on developing career of young dentists. Hence, the contribution of dentists beyond dental practice in this pandemic situation will be appreciated by future generations.